Neurotoxicity and neuroprotective effects of Polyimides (PI) and Polyphenylenevinylene (PPV) against Hydrogen Peroxide (H2O2) / Norfaezah Mazalan ... [et al.] - Mazalan, Norfaezah; Mat Zain, Mazatulikhma; Jumali, Nor Saliyana; Mohalid, Norhanim; Shameri, Zurina; Hamzah, Ahmad Sazali (Research Management Institute (RMI), 2011)
Recently, research and development in the field of drug delivery systems (DDS) facilitating site-specific therapy has reached significant progression. DDS based on polymer micelles, coated micro- and nanoparticles, and various prodrug systems including water-soluble polymer have been prepared and extensively studied as novel drugs designed for cancer chemotherapy and brain delivery. Since polymers are going to be used in human, this study has the interest of testing two types of polymer, polyimides (PI) and polyphenylenevinylene (PPV) on neuronal cells. The objective of this study was to determine the possible neurotoxicity and potential neuroprotective effects of PI and PPV towards SH-SY5Y neuronal cells challenged by hydrogen peroxide (H2O2) as an oxidant. Cells were pretreated with either PI or PPV for 1 hour followed by incubation for 24 hour with 100 μM of H2O2. MTS assay was used to assess cell viability. Results show that PI and PPV are not harmful within the concentration up to 10 μM and 100 μM, respectively. However, PI and PPV do not protect neuronal cells against toxicity induced by H2O2 or further up the cell death.